Tinjauan Penerapan Sistem Manajemen Keselamatan Dan kesehatan Kerja (SMK3) (Studi kasus: Pembangunan Rumah Sakit Umum Daerah Pekanbaru) - Suci Restu Miswati Jusan; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pekanbaru is one of the fastest—growing city in Indonesia in term of construction development. To support it, government builds the public hospital which is located in Garuda Sakti street Pekanbaru. The project had more than 100 workers and another 100 workers are working with the heavy equipment so that can put them in danger and give an high risk for their safety and comfort. To minimizing number of the accident in the working place and to realization the zero accident, it is require the implementation of SMK3 in that project. The method in this research is quantitative and univary analysis method and also descriptive qualitative method. Dissemination of the questionnaire was addressed to 101 construction workers and 20 staff in the project. The Implementation assessment result SMK3 base on PP No. 50 in 2012 showed 60,13% and classified as GOOD application level. The result of SMK3 audit assessment in RSUD Pekanbaru is 81,32% and classified as GOOD application level as well. In the assessment of the audit result found 30 criteria that wasn’t match with the minor and another 1 criteria wasn’t match with the major criteria. Pursuant to the results of calculation analysis tools and equipment procurement costs K3 is Rp.78.036.00,00 or 0.002% from the total value of the project contract. Factors that inhibit the implementation of SMK3 is psychological factors of the workers and the environmental factors of the project.Keywords: Hospital Pekanbaru, Zero accident, SMK3, Evaluation, Audit